(untitled) (Research, Society and Development, 2021)
Growing informal urbanization poses a significant challenge to environmental governance in the Global South. This paper examines the theoretical literature linking environmental governance to informal settlements and social exclusion in cities. Though the research output on environmental governance is growing, the attention is mainly focused on cities of the Global North, while theoretical insights and empirical data on cities of the Global South is still far from adequate. In a search of publications of the last decade in Scopus and Web of Science, only 1% of the research output on environmental governance addresses informal settlements. The mechanisms of environmental modernization and ecosocialism are considered for suitability to address environmental challenges where informal settlements are widespread. The relevance of these mechanisms and existing theoretical frameworks for anticipating urban governance responsiveness to environmental pressures in the Global South is unknown. The paper creates awareness of the need for future research on urban governance where informal settlements are the norm. This is relevant for scholars working on the Sustainable Development Goals at city scale.